1993
DOI: 10.1507/endocrj.40.17
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly with Hyperprolactinemia Developed after Bilateral Adrenalectomy in a Patient with Cushing's Syndrome due to Adrenocortical Nodular Hyperplasia.

Abstract: Abstract. A 27-yr-old woman was referred for evaluation of acromegaly and hyperprolactinemia. She had undergone left adrenalectomy at 12 and right adrenalectomy at 17 for Cushing's syndrome due to adrenocortical nodular hyperplasia. At this time a pituitary tumor was found by brain computerized tomography, but plasma levels of growth hormone (GH), prolactin (PRL) and adrenocorticotropin (ACTH) were normal. When she was 23, symptoms and signs of acromegaly and subsequently galactorrhea-amenorrhea had developed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Previously reported cases suffering from both of these endocrinopathies included patients with an ectopic ACTH-and GH-producing tumor (4, 5), pituitary tumors secreting both human GH and ACTH (6, 7), or pituitary tumors secreting GH and ACTH-independent adrenal hypersecretion (8)(9)(10). In the present report, we describe a rare case of pre-clinical Cushing's syndrome caused by an adrenal adenoma discovered a few years after transsphenoidal selective removal of a pituitary adenoma for acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported cases suffering from both of these endocrinopathies included patients with an ectopic ACTH-and GH-producing tumor (4, 5), pituitary tumors secreting both human GH and ACTH (6, 7), or pituitary tumors secreting GH and ACTH-independent adrenal hypersecretion (8)(9)(10). In the present report, we describe a rare case of pre-clinical Cushing's syndrome caused by an adrenal adenoma discovered a few years after transsphenoidal selective removal of a pituitary adenoma for acromegaly.…”
Section: Discussionmentioning
confidence: 99%
“…In CNC this course is even slower and acromegaly is often unmasked by adrenalectomy for primary pigmented nodular adrenocortical disease (PPNAD) [27]. In our prospective evaluation of patients with CNC, we have had the opportunity to observe the "development" of pituitary adenomas, so far in 4 patients.…”
Section: Overviewmentioning
confidence: 99%
“…In contrast, hypoprolactinemia seems to inhibit the hypothalamohyophyseal-adrenal axis. It had been shown that bro-mocriptine suppresses the plasma ACTH concentration in patients with Cushing disease and Nelson's syndrome [16][17][18]. Additionally, treatment with bromocriptin for 6 days significantly reduced both PRL and cortisol concentrations in castrated pigs [19].…”
mentioning
confidence: 99%